O-072 Characteristics of a COVID-19 cohort with large vessel occlusion: a multicenter international study. (23rd July 2022) - Jabbour, P; Dmytriw, A; Sweid, A; Piotin, M; Bekelis, K; Sourour, N; Raz, E; Linfante, I; Kole, M; Nimjee, S; Lopes, D; Hassan, A; et al.
Abstract : Background: The mechanisms and outcomes in COVID-19-associated stroke are unique from those of non-COVID-19 stroke. Objectives: The purpose of this study is to describe the efficacy and outcomes of acute revascularization of large vessel occlusion (LVO) in the setting of COVID-19 in an international cohort. Methods: We conducted an international multicenter retrospective study of consecutively admitted COVID-19 patients with concomitant acute large vessel occlusion (LVO) across 50 comprehensive stroke centers. Our control group constituted historical controls of patients presenting with LVO and receiving a MT between January 2018 to December 2020.Results: The total cohort was 575 patients with acute LVO, 194 had COVID-19 while 381 patients did not. Patients in the COVID-19 group were younger (62.5 vs. 71.2; p<0.001), and lacked vascular risk factors (49, 25.3% vs. 54, 14.2%; p =0.001). mTICI 3 revascularization was less common in the COVID-19 group (74, 39.2% vs. 252, 67.2%; p < 0.001). Poor functional outcome at discharge (defined as mRS 3–6) was more common in the COVID-19 group (150, 79.8% vs.132, 66.7%; p =0.004). COVID-19 was independently associated with a lower likelihood of achieving mTICI 3 (OR: 0.4, 95% CI: 0.2 –0.7; p<0.001), and unfavorable outcomes (OR: 2.5, 95% CI: 1.4 – 4.5; p=0.002). Conclusion: COVID-19 was an independent predictor of incomplete revascularization and poor outcomes in patients with stroke due to LVO. COVID-19 patients with LVO patients were younger, had fewer cerebrovascular risk factors, and suffered from higher morbidity/mortality rates. Disclosures: P. Jabbour: 2; C; Medtronic, Microvention, Balt, Cerus Endovascular. A. Dmytriw: None. A. Sweid: None. M. Piotin: None. K. Bekelis: None. N. Sourour: None. E. Raz: None. I. Linfante: None. M. Kole: None. S. Nimjee: None. D. Lopes: None. A. Hassan: None. P. Kan: None. M. Ghorbani: None. M. Levitt: None. A. Pandey: None. R. Starke: None. K. El Naamani: None. R. Abbas: None. O. Mansour: None. M. Walker: None. M. Heran: None. A. Kuhn: None. B. Menon: None. S. Sivakumar: None. A. Mowla: None. A. Zha: None. D. Cooke: None. A. Siddiqui: None. G. Gupta: None. C. Tiu: None. P. Portela: None. N. De la Ossa: None. X. Orra: None. M. De Lera: None. M. Ribo: None. M. Piano: None. K. De Sousa: None. F. Al Mufti: None. Z. Hashim: None. L. Renieri: None. T. Nguyen: None. P. Feineigle: None. A. Patel: None. J. Grossberg: None. H. Saad: None. M. Gooch: None. S. Tjoumakaris: None. N. Herial: None. R. Rosenwasser: None.